Green tea extract suppresses airway inflammation via oxidative stress-driven MAPKs/MMP-9 signaling in asthmatic mice and human airway epithelial cells - Kim, Jeong-Won; Kim, Jin-Hwa; Jeong, Ji-Soo; Kim, Chang-Yeop; Chung, Eun-Hye; Kim, Sung-Hwan; Hong, Eui-Ju; Kwon, Hyo-Jung; Ko, Je-Won; Kim, Tae-Won (Frontiers in Immunology, 2024)
Introduction The anti-inflammatory effect of green tea extract (GTE) has been confirmed in asthmatic mice, however, the pharmacological mechanism is not fully elucidated. Methods To investigate the therapeutic efficacy of GTE in asthma and identify specific pathways, murine model of allergic asthma was established by ovalbumin (OVA) sensitization and the challenge for 4 weeks, with oral treatment using GTE and dexamethasone (DEX). Inflammatory cell counts, cytokines, OVA-specific IgE, airway hyperreactivity, and antioxidant markers in the lung were evaluated. Also, pulmonary histopathological analysis and western blotting were performed. In vitro, we established the model by stimulating the human airway epithelial cell line NCI-H292 using lipopolysaccharide, and treating with GTE and mitogen-activated protein kinases (MAPKs) inhibitors. Results The GTE100 and GTE400 groups showed a decrease in airway hyperresponsiveness and the number of inflammatory cells in the bronchoalveolar lavage fluid (BALF) compared to the OVA group. GTE treatment also reduced interleukin (IL)‐13, IL-5, and IL‐4 levels in the BALF, and OVA-specific immunoglobulin E levels in the serum compared to those in the OVA group. GTE treatment decreased OVA-induced mucus secretion and airway inflammation. In addition, GTE suppressed the oxidative stress, and phosphorylation of MAPKs, which generally occurs after exposure to OVA. GTE administration also reduced matrix metalloproteinase‐9 activity and protein levels. Conclusion GTE effectively inhibited asthmatic respiratory inflammation and mucus hyperproduction induced by OVA inhalation. These results suggest that GTE has the potential to be used for the treatment of asthma.